Infra-estrutura verde na paisagem urbana contemporânea : o desafio da conectividade e a oportunidade da multifuncionalidade - Madureira, Helena (2012)
The main objective of this paper is to introduce, discuss and develop the "green infrastructure" concept, trying to frame it as an aggregating concept of other previous approaches, while also specifying the reasons for the emergence of this new designation in the context of urban green areas planning approaches. After a reflection on the origin of the concept, we discuss its three fundamental dimensions. Firstly, we define the challenge of continuity/connectivity of urban green areas as a value simultaneously ecological, social and for urban composition. Secondly, we present the opportunity of the multifunctionality in a sprawled city, which inherently has a greater structural and functional diversity of green areas. Thirdly, and as a corollary, we justify the need to face the urban green areas network as an infrastructural system in the contemporary city.